A Trusted IoT Communication Architecture Based on Blockchain and Named Data Network. Issue 1 (1st April 2022) - Sun, Yizhe; Chen, Shiyou; Fang, Yadong; Xu, Wei; Luo, Qun; Rui, Lanlan
Abstract: The trusted cross-domain sharing capability of the Internet of Things (IoT) terminals needs to be improved urgently. Aiming at the technical issues of routing overhead and authentication security of data sharing of IoT devices, this paper proposes a trusted transmission architecture for network-chain collaboration. Introduce the mobile edge computing (MEC) platform in named data network (NDN) to deploy blockchain light nodes and improve the PBFT consensus algorithm. Besides, a cross-domain authentication algorithm based on elliptic curve encryption is proposed. Simulation results show that the improved PBFT and cross-domain authentication algorithm can effectively improve IoT cross-domain sharing capabilities.